Implementasi Model Discovery Learning dalam Pembelajaran Bahasa Indonesia Materi Teks Eksplanasi Kelas IX di SMP - Dewi Rahmawati; Rustam Rustam; Lusia Oktri Wini (MAN 4 Kota Pekanbaru, 2026)
This study aims to describe the implementation of the Discovery Learning model in Indonesian language learning on explanatory text materials for Grade IX students at SMP Negeri 25 Jambi City. The research employed a qualitative approach using a case study design. Data were collected through classroom observations, semi-structured interviews, and documentation. The participants consisted of one Indonesian language teacher and Grade IX students selected purposively. Data validity was ensured through source and technique triangulation, while data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that the Discovery Learning model was implemented according to its six stages: stimulation, problem statement, data collection, data processing, verification, and generalization. The model successfully encouraged students to participate actively, think critically, collaborate during discussions, and better understand the structure and language features of explanatory texts. However, several challenges remained, including differences in students' learning abilities, limited instructional time, and varying levels of participation during group discussions. Overall, the implementation of the Discovery Learning model supports the objectives of the Merdeka Curriculum by promoting student-centered learning and improving the quality of Indonesian language instruction.